2018
DOI: 10.3390/cancers10070238
|View full text |Cite
|
Sign up to set email alerts
|

Micelles Structure Development as a Strategy to Improve Smart Cancer Therapy

Abstract: Micelles as colloidal suspension have attracted considerable attention due to their potential use for both cancer diagnosis and therapy. These structures have proven their ability to deliver poorly water-soluble anticancer drugs, improve drug stability, and have good penetration and site-specificity, leading to enhance therapeutic efficacy. Micelles are composed of hydrophobic and hydrophilic components assembled into nanosized spherical, ellipsoid, cylindrical, or unilamellar structures. For their simple form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
88
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 207 publications
(102 citation statements)
references
References 110 publications
0
88
0
Order By: Relevance
“…Promising DDSs are metallopolymers based on polymer micelles. 137,138 In particular, covalent attachment of a drug directly to a micelle is of interest to avoid its premature release in the circulation. So, poly(ethylene glycol)-block-PGA (PEG-b-PGA) was used as leaving group of the Pt(II) drugs of cisplatin and oxaliplatin.…”
Section: Metal-containing Synthetic Polymersmentioning
confidence: 99%
“…Promising DDSs are metallopolymers based on polymer micelles. 137,138 In particular, covalent attachment of a drug directly to a micelle is of interest to avoid its premature release in the circulation. So, poly(ethylene glycol)-block-PGA (PEG-b-PGA) was used as leaving group of the Pt(II) drugs of cisplatin and oxaliplatin.…”
Section: Metal-containing Synthetic Polymersmentioning
confidence: 99%
“…Poly(acrylic acid) (PAA) is a hydrophilic polymer [56] that adopts a random coil conformation in solution. In their recent work, Hanafy and his colleagues have further demonstrated that these coils have swelling properties under certain ionic strengths and salt concentrations, leading to extended chain conformations in alkaline solutions (Figure 4) [49,[57][58][59]. This is due to the COOH side chain which is pH responsive, i.e., protonated (COOH) at pH ≤5while de-protonated (COO-) at pH >5 [60].…”
Section: Mucoadhesion and Its Relation With Certain Polymersmentioning
confidence: 99%
“…They are composed of a monolayer of amphiphilic molecules that spontaneously tend to self-assemble in aqueous environments at a definite concentration, known as critical micelle concentration (CMC). These amphiphilic molecules are generally fatty acids, salts of fatty acid (soaps), phospholipids, or other similar amphiphilic compounds [37]. Micelles present either a hydrophobic core, exposing outside the hydrophilic polar heads, or a hydrophilic core, exposing outside the hydrophobic tails (inverted micelles) ( Figure 2) [38].…”
Section: Micellesmentioning
confidence: 99%